Stress and job performance in the public sector in the world. A systematic review of the literature from 2021-2024 - Espinoza Aguilar, Jorge Luis; Flores Ocaña, Avelino Jaimito; Méndez-Gutiérrez, Leidy Lucia (LACCEI, 2024)
This study focuses on examining the impact of stress on job performance in the public sector globally during the period from 2021 to 2024. Using the PRISMA methodology, a systematic review of the literature was carried out, selecting 118 documents from the 50 found. The results highlight a significant association between stress and job performance, identifying work overload and adverse working conditions as main factors. The discussion of the findings emphasizes the importance of implementing measures to mitigate stress and improve the work environment, which could lead to substantial improvements in organizational performance. It is concluded that addressing work stress is crucial to promoting health and effectiveness in the public sector globally, highlighting the need for work policies and practices that prioritize employee well-being. In summary, this study highlights the urgency of preventive and intervention actions to optimize work performance and guarantee the mental health of public sector workers.